(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: Teachers working with students who have intellectual disabilities are the pillars supporting these students throughout their educational success and are primarily responsible for implementing transition plans for them. The ability of teachers working with students who have intellectual disabilities to acquire competencies related to student transition to different stages is a primary factor that makes this transition smooth. Therefore, teaching self-efficacy plays a crucial role in teachers’ success in their assigned roles and, accordingly, implementing transition plans. Objective: The study aimed to examine the effectiveness of a training program in equipping teachers working with students who have intellectual disabilities with competencies for implementing transition plans and enhancing their self-efficacy. Methods: The study adopted the quasi-experimental approach that included one experimental group subject to pre-test and post-test measurements and a follow-up measurement to evaluate the effectiveness of the training program and its sustainable results. In this study, the independent variable was the training program, while the dependent variables were the competencies for implementing transition plans and teaching self-efficacy. The study employed the following instruments: a questionnaire on the competencies of teachers of students with intellectual disabilities for implementing transition plans (developed by the researchers), a questionnaire on teaching self-efficacy among special education teachers (developed by the researchers), and a training program (developed by the researchers). Participants: The study sample comprised (13) elementary-stage teachers working with students with intellectual disabilities. The teachers demonstrated insufficient competencies in implementing transition plans and insufficient teaching self-efficacy. Results: The study’s results confirmed the effectiveness of the training program in improving teachers’ competencies for implementing transition plans and teaching self-efficacy. This is indicative of the effectiveness of the activities and strategies included in the program in enhancing these competencies and skills for the teachers. Conclusions: The study at hand is one of the few that contributes to the professional development of teachers working with students with intellectual disabilities in an Egyptian environment. The study also presented two measuring instruments: one for transition competencies, another for teaching self-efficacy, and a training program for enhancing both.